Investigating EFL oral production in a technology mediated TBLT context - Albarqi Ghadah (Journal of China Computer-Assisted Language Learning)
In the rapidly expanding domain of online learning, investigating the effectiveness of technology-mediated task-based language teaching (TBLT) in improving English as a Foreign Language (EFL) oral production becomes paramount. Therefore, the present study was conducted over two months to examine how EFL learners’ oral production, measured by complexity, accuracy, and fluency (CAF), changed throughout technology-mediated TBLT instructions. This study also examined how the relationships among CAF aspects evolved. A cohort of 38 EFL learners underwent a series of oral tasks at the beginning and end of the study period, and repeated measures and correlation analyses were employed to analyse the data. The findings showed significant improvement in EFL learners’ speech rate and accuracy of their utterances after two months. Moreover, the data indicated that fluency features were intricately connected with other CAF dimensions, whereas accuracy, lexical diversity, and syntactic complexity exhibited independent development. The identification of long-term relationships among certain CAF aspects provided valuable insights into the underlying mechanisms of EFL speech production. The results of this study have significant implications for both research and practice within the domain of technology-mediated TBLT.